Benthic macroinvertebrate community structure and distribution in Sungai Pichong, Gunung Chamah, Kelantan, Malaysia - Aweng Eh Rak; Suhaimi, O.; Nur Izzati, S (2012)
The study was to assess the Benthic macroinvertebrate species and compositions in the highland river (Sungai Pichong) which located about 800 meter above mean sea level to be used as biological indicators for water quality assessment and also to determine the physical water quality factor that influence benthic organism compositions and distributions. The study was carried out on 25 July 2011 till 27 July 2011. Four sampling points 200 meters apart were fixed by Global Positioning Systems (GPS). There was no significant difference for in-situ water quality reading between sampling station as well as the date of sampling. Based on in-situ parameters which was compared with Interim National Water Quality Standard for Malaysia was found that Sungai Pichong could be categorized under Class I, river which has excellent water quality. In addition, a total of nine families and 137 individual taxa were identified and of these, three families belonged to the order ephermeroptera (caenidae, baetidae and siphlonuridae) and dipteral (chironominae, tabanidae and tipulidae), two families to coleopteran (elmidae and gyrinidae) and one family to odonata (aeshnidae). Only one taxa present to indicate an excellent river health namely ephermeroptera. Normally, there were three taxa namely ephermeroptera, plecoptera and trichoptera (EPT) present in healthy river. On the other hand, the SIGNAL score at all stations was recorded between 5 and 6 which was fall under mild pollution category.